Intercultural collective action: methodological reflections of and with the Congress of the Peoples' Movement (Colombia) - Cortés, German Andrés (Revista Extraprensa, 2018)
The following work is the product of the reflections made from the project "The Congress of Peoples, intercultural collective action and emerging political subjectivities", which includes participatory and active methodological expressions and forms that involve rural and urban actors belonging to the social movement. CP as indigenous, peasants and Afro-Colombians. This reflection is carried out within the framework of the last stage of the project, in which the analysis is established between the categories of collective action, interculturality and political subjectivities, especially from the dimensions of political consciousness.